Eruptive styles of subduction-zone volcanoes : investigation of magmatic volatile budgets and ascent rates using apatite - Li, Weiran (2019)
The most explosive and dangerous volcanoes around the world are located at subduction zones. Understanding the changes in their eruption dynamics has great significance for mitigating volcanic hazards. In this thesis I investigate the role of volatiles on volcanic eruptions using a combination of thermodynamic, experimental, and observational approaches. First, I propose a new thermodynamic model of the partition behaviour of F-Cl-OH between apatite and melt to estimate the melt water contents. This model includes a treatment of the thermodynamically non-ideal properties of the ternary apatite at magmatic temperatures, and it has been developed as a free web-based calculator. Second, I use the thermodynamic model and various crystal chemistry data to calculate the melt volatile budgets of two eruptions of distinct styles at Merapi volcano (Indonesia). I characterise for the first time the CO2, H2O, S, Cl and F contents of the deep melts (near the Moho) below this volcano. Fluxing of these deep volatiles to the shallower magmatic system is likely the cause of the large and explosive 2010 eruption. Third, I report new experimental results for the diffusion coefficients of F, Cl, OH and S in apatite at magmatic temperatures. I find that these volatiles re-equilibrate via a multicomponent diffusion mechanism. Application of the new diffusion data to zoning of volatiles in natural apatite allows determination of the timescales of magma ascent. I believe that the results from this Ph.D. thesis provide new insights into the plumbing system, magmatic volatile budgets and magma ascent rates of subduction-zone volcanoes, and also help to improve the interpretation of volcanic monitoring data that is critical for eruption forecasting.